Persisting Antibody Response to SARS-CoV-2 in a Local Austrian Population - Ladage, Dennis; Rösgen, Delia; Schreiner, Clemens; Ladage, Dorothee; Adler, Christoph; Harzer, Oliver; Braun, Ralf J. (Frontiers in Medicine, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a global pandemic recently. The prevalence and persistence of antibodies following a peak SARS-CoV-2 infection provides insights into the potential for some level of population immunity. In June 2020, we succeeded in testing almost half of the population of an Austrian town with a higher incidence of COVID-19 infection. We performed a follow-up study to reassess the prevalence of SARS-CoV-2-specific IgA and IgG antibodies with 68 participants of the previous study. We found that the prevalence of IgG or IgA antibodies remained remarkably stable, with 84% of our cohort prevailing SARS-CoV-2-specific antibodies (only a slight decrease from 93% four months before). In most patients with confirmed COVID-19 seroconversion potentially provides immunity to reinfection. Our results suggest a stable antibody response observed for at least six months post-infection with implications for developing strategies for testing and protecting the population.